Microspheres prepared with biodegradable PHBV and PLA polymers as prolonged-release system for ibuprofen: in vitro drug release and in vivo evaluation - Giovana Carolina Bazzo; Aline Teixeira de Macedo; Janine Paula Crenca; Virgínia Emiliana Silva; Eduardo Manoel Pereira; Melissa Zétola; Bianca Ramos Pezzini (Universidade de São Paulo, 2012)
In this study, poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) and poly(l-lactide) (PLA) microspheres containing ibuprofen were prepared with the aim of prolonging the drug release. The oil-in-water (O/W) emulsion solvent evaporation technique was used, varying the polymer ratio. All formulations provided spherical particles with drug crystals on the surface and a porous and rough polymeric matrix when PHBV was used and smooth external surface when prepared with PLA. The in vitro dissolution profiles show that the formulation containing PHBV/PLA at the proportion of 30/70 presented the best results in terms of prolonging the ibuprofen release. The analysis of the concentration of ibuprofen in the blood of rats showed that maximum levels were achieved at between one and two hours after administration of the immediate-release form (pure drug), while the prolonged microspheres led to a small amount of the drug being released within the first two hours and reached the maximum level after six hours of administration. It was concluded that it is possible to prolong the release of ibuprofen through its incorporation into PHBV/PLA microspheres. No presente estudo foram preparadas microesferas de poli(hidroxibutirato-co-hidroxivalerato) (PHBV) e poli(ácido láctico) (PLA) com o objetivo de prolongar a liberação do ibuprofeno, utilizado como fármaco modelo. Empregou-se o método de emulsificação e evaporação do solvente óleo em água (O/A), variando-se a proporção entre os polímeros. Todas as formulações originaram partículas esféricas com cristais de fármaco aderidos à superfície externa. As microesferas apresentaram superfície rugosa e porosa, quando o PHBV foi utilizado, e superfície externa lisa, quando preparadas com o PLA. Os perfis de dissolução in vitro evidenciaram que a formulação que continha PHBV/PLA na proporção de 30/70 apresentou melhores resultados para prolongar a liberação do ibuprofeno. Através da análise da concentração de ibuprofeno no plasma de ratos, após administração oral, verificou-se que os níveis máximos ocorreram entre 1 e 2 horas após a administração de ibuprofeno não encapsulado, enquanto o fármaco presente nas microesferas atingiu um pico máximo após 6 horas da administração. Conclui-se, portanto, que é possível prolongar a liberação do ibuprofeno após a sua incorporação às microesferas preparadas com os polímeros PHBV e PLA, especialmente na proporção de 30/70.